Interleukin-21 receptor-mediated signals control autoreactive T cell infiltration in pancreatic islets - Van Belle, Tom L; Nierkens, Stefan; Arens, Ramon; von Herrath, Matthias G (Immunity (Cambridge, Mass.), 2012)
It remains unclear how interleukin-21 receptor (IL-21R) contributes to type 1 diabetes. Here we have shown that dendritic cells (DCs) in the pancreas required IL-21R not for antigen uptake, but to acquire the chemokine receptor CCR7 and migrate into the draining lymph node. Consequently, less antigen, major histocompatibility complex (MHC) class II, and CD86 was provided to autoreactive effector cells in Il21r(-/-) mice, impairing CD4(+) T cell activation, CD40:CD40L interactions, and pancreatic infiltration by autoreactive T cells. CD40 crosslinking restored defective CD4(+) cell expansion and CD4 independently expanded autoreactive CD8(+) cells, but CD8(+) cells still required CD4(+) cells to reach the pancreas and induce diabetes. Diabetes induction by transferred T cells required IL-21R-sufficient host antigen-presenting cells. Transferring IL-21R-sufficient DCs broke diabetes resistance in Il21r(-/-) mice. We conclude that IL-21R controls both antigen transport by DCs and the crucial beacon function of CD4(+) cells for autoreactive CD8(+) cells to reach the islets.